2010
DOI: 10.1002/jor.21135
|View full text |Cite
|
Sign up to set email alerts
|

Individual susceptibility to periprosthetic osteolysis is associated with altered patterns of innate immune gene expression in response to pro‐inflammatory stimuli

Abstract: Susceptibility to osteolysis after total hip arthroplasty (THA) varies between individuals. We examined whether patients susceptible to osteolysis (group I, n ¼ 34 subjects) after cemented Charnley THA have quantitatively different innate immune responses to pro-inflammatory stimuli versus patients without this susceptibility (group II, n ¼ 28 subjects) at a mean of 14 years after primary surgery. Extracted peripheral blood mononuclear cells were stimulated for 3 h using endotoxin (lipopolysaccharide-LPS, 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 28 publications
3
28
0
2
Order By: Relevance
“…This might suggests that fluid pressure recruited cells mainly from the bone marrow meanwhile titanium particles seemed to recruit cells from the soft tissue beneath the piston. We corroborated that titanium particle-induced osteolysis displays an up-regulation of a pro-inflammatory response and subsequent osteoclast activation as previously described in both animal models [Taki et al, 2005] and in vitro studies [Gordon et al, 2010]. TNFa, IL-1, and IL-6 were all up regulated at the mRNA level after 24 h, which might be related to osteoblastic and/or macrophage-driven stimulation of osteoclastogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…This might suggests that fluid pressure recruited cells mainly from the bone marrow meanwhile titanium particles seemed to recruit cells from the soft tissue beneath the piston. We corroborated that titanium particle-induced osteolysis displays an up-regulation of a pro-inflammatory response and subsequent osteoclast activation as previously described in both animal models [Taki et al, 2005] and in vitro studies [Gordon et al, 2010]. TNFa, IL-1, and IL-6 were all up regulated at the mRNA level after 24 h, which might be related to osteoblastic and/or macrophage-driven stimulation of osteoclastogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…However, those studies also showed that other factors modulate the biologic response to wear particles. Also consistent with the importance of other factors is the finding that monocyte production of proinflammatory cytokines in response to polyethylene and titanium wear particles varies greatly between individual donors [31,46]. The similar finding with different types of particles is not surprising because the different types of particles are thought to induce osteolysis through similar proinflammatory mechanisms [7,75,102,108].…”
Section: Introductionsupporting
confidence: 58%
“…But patients shows different responses to inflammatory stimuli [12,13]. This may introduce bias into certain study designs.…”
Section: Discussionmentioning
confidence: 99%
“…Gordon et al were determined, patients had different responses to inflammatory stimuli [13]. There are some individual differences against to inflammation between patients, therefore NLR will vary from person to person in response to inflammatory stimuli.…”
Section: Introductionmentioning
confidence: 99%